Legal description of categories of honor and dignity in the development of administrative law - Осипенко, Наталія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article the author makes the analysis of some aspects of the legislative adjusting of honour and dignity in national legislation. Are pointed determinations of honour and dignity, which are in scientific legal literature. The author consider vexed questions, which arise in practice at application of the national legislation.